Growth of entire solutions of singular initial-value problem in several complex variables - Devendra Kumar; Mohammed Harfaoui (Electronic Journal of Differential Equations, 2012)
In this article, we characterize the order, type, lower order, and lower type of entire function solutions to a class of singular initial-value problems, in terms of multinomials for $ngeq 2$.